2014
DOI: 10.4049/jimmunol.1400516
|View full text |Cite
|
Sign up to set email alerts
|

Two Functionally Distinct Subsets of Mast Cells Discriminated By IL-2–Independent CD25 Activities

Abstract: We identified two mast cell subsets characterized by the differential expression of surface CD25 (IL-2Rα) and by different abilities to produce cytokines and to proliferate, both in vitro and in vivo. CD25 can be expressed on the surface of immune cells in the absence of the other chains of the IL-2R, which are indispensable for IL-2 signaling. We show that functional differences between the two mast cell populations were dependent on CD25 itself, which directly modulated proliferation and cytokine responses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…First, we evaluated cell survival in response to withdrawal of IL-3, which was unaffected by Tet2 deletion (Figure S2A). Conversely, by assessing BrdU incorporation in response to IL-3 treatment (Figure S2B) (Deho' et al, 2014), we found that Tet2 −/− mast cells showed significant hyperproliferation compared to their Tet2 +/+ counterparts, while Tet2 +/− cells displayed an intermediate phenotype, pointing again toward a gene-dosage effect of Tet2 in regulating mast cellproliferation (Figures 1D and 1E). …”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…First, we evaluated cell survival in response to withdrawal of IL-3, which was unaffected by Tet2 deletion (Figure S2A). Conversely, by assessing BrdU incorporation in response to IL-3 treatment (Figure S2B) (Deho' et al, 2014), we found that Tet2 −/− mast cells showed significant hyperproliferation compared to their Tet2 +/+ counterparts, while Tet2 +/− cells displayed an intermediate phenotype, pointing again toward a gene-dosage effect of Tet2 in regulating mast cellproliferation (Figures 1D and 1E). …”
Section: Resultsmentioning
confidence: 96%
“…Cell differentiation was monitored by surface staining of relevant mast cell and myeloid markers (Figure 1A). In these culture conditions, more than 90% of WT ( Tet2 +/+ ) cells differentiated to mast cells (Kit + FcεRIα + ) by the end of the third week of culture (Figures 1A–1C) (Deho' et al, 2014; Mayoral et al, 2011; Mayoral and Monticelli, 2010; Rusca et al, 2012); however, Tet2 −/− cultures showed reduced percentages of mast cells, as well as aberrant expression of markers for other myeloid cells (Mac1 and Ly6G) (Figure 1A), suggesting delayed or altered differentiation. Cultures from heterozygous littermates showed an intermediate phenotype, pointing toward a gene-dosage effect of Tet2 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations